Absorptive Capacity and Sustainable Competitive Advantage through Market Orientation and Dynamic Capability in MSMEs - Onita Sari Sinaga; Christina Yanita Setyawati; Rr. Chusnu Syarifa Diah Kusuma; Acai Sudirman (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study examines the direct and mediating effects of market orientation, dynamic capability, and absorptive capacity on sustainable competitive advantage among Micro, Small, Medium-Sized Enterprises (MSMEs).Research Methodology: Employing a quantitative explanatory approach, this study analyzes data from 280 purposively selected MSMEs using structured questionnaires and Partial Least Squares Structural Equation Modeling (PLS-SEM).Results: The findings indicate that market orientation significantly enhances absorptive capacity by improving firms’ ability to acquire, assimilate, and utilize external knowledge. Market orientation and dynamic capability also positively affect sustainable competitive advantage, while absorptive capacity partially mediates these relationships.Conclusions: MSMEs need to strengthen market knowledge, organizational flexibility, and knowledge management capabilities to maintain long-term competitiveness.Limitations: The cross-sectional design and industry-specific context may limit the generalizability of the findings across different sectors and regions.Contributions: This study contributes to the Knowledge-Based View (KBV) and Dynamic Capability Theory (DCT) by explaining how knowledge utilization and adaptive capabilities generate sustainable competitive advantage. It also provides practical implications for MSME managers in improving strategic responsiveness and organizational adaptability.